Effects of conjugated fatty acid supplementation on central obesity and blood pressure in women with benign breast disease: a randomized controlled-clinical trial - Pirouzpanah, Saeed; Montazeri, Vahid; Baradaran, Behzad; Taghizadeh, Mohsen; Rezvani, Neda (Progress in Nutrition, 2018)
Objective: Health benefits of conjugated fatty acids, particularly conjugated linolenic acid (CLNA), have recently provide substantial insights in a variety of obesity-related tumorigenesis including breast neoplasia. This study aims to investigate the effects of CLNA-contained oil (CLNAO) supplementation on central obesity indices and blood pressure in women with benign breast disease (BBD). Methods: Forty six pre-menopausal women with BBD were randomly allocated to intervention group (n=23) or placebo (n=23). Patients in the intervention group received 1000 mg/day CLNAO capsule and the placebo group received 1000 mg/day inert oil-contained capsule during 13 weeks. Measures of blood pressure and some anthropometric variables were performed at the baseline and end of study. Result: Systolic (P<0.01) and diastolic (P<0.05) blood pressures decreased within CLNAO group on subjects whom were overweight. Normal weight participants who received placebo showed significant increases in total body fat (P<0.05), waist circumference (P<0.05), and waist circumference to height ratio (P<0.05), meantime CLNAO group showed no changes on both variables. Intervention with CLNAO caused no significant increases on skinfolds of abdomen and suprailiac, whereas these measures were remarkably increased in placebo (P<0.001 and P<0.05, respectively). Conclusion: Findings from this study show that CLNAO can attenuate development of central fat acquisition in the BBD patients who weighted normally. Administration of CLNAO decline systolic and diastolic blood pressures of overweight subjects.